Indacenodithienothiophene-based A-D-A-type phototheranostics for immuno-phototherapy - Yangtian Ye; Shaojing Zhao; E Pang; Yuanyu Tang; Pan Zhu; Wenjie Gao; Qingxu Diao; Jie Yu; Jie Zeng; Minhuan Lan; Jianing Yi (Journal of Nanobiotechnology)
Abstract The development of phototherapeutics with high photothermal conversion efficiency (PCE) and strong ability to generate reactive oxygen species under single near-infrared (NIR) laser irradiation for immuno-phototherapy applications remains a significant challenge. Herein, we optimally selected the molecule IT-4 F with an acceptor-donor-acceptor (A-D-A) strucssture to prepare water-dispersible nanoparticles (NPs) by assembly with DSPE-PEG-NH2. Such NPs have NIR absorption and fluorescence peaks at 728 and 817 nm, respectively. They can generate singlet oxygen (1O2) and superoxide anion (O2 −·) under laser irradiation, with a 1O2 generation quantum yield of 31.5%. They can also effectively convert photon-energy into heat with a high PCE of 42.8%. The outstanding properties of IT-4 F NPs enable them to be used in NIR fluorescence imaging guided photothermal therapy (PTT), and photodynamic therapy (PDT). Moreover, PDT and PTT triggered immunogenic cell death and PANoptosis in tumor cells, which not only inhibited tumor growth and metastasis in mice model, but also induced a robust immune response, evidenced by increased infiltration of CD8+ T cells, CD4+ T cells, dendritic cells, and a decreased presence of immunosuppressive cells such as myeloid-derived suppressor cells and regulatory T cells. The efficacy of IT-4 F NPs in organoid of human breast cancer was also verified. Graphical abstract